Sistem Monitoring Keamanan Pada Green House - Adhy, Dewanto Rosian; Hermawan, Rudi; Fauzi, Ahmad Miftah; Maesaroh, Siti; Mauhib, Akpil; Rosada, Nyataku Ibnu; Suhendar, Asep; Noor, Yudin Wahyudin (Politeknik Harapan Bersama Tegal, 2024)
This study aims to develop a security monitoring system for greenhouses using Internet of Things (IoT) technology. The system utilizes motion sensors to monitor activity, with the ESP32 Cam module implemented within the greenhouse. Data from the ESP32 Cam is processed using object detection algorithms to identify and track any objects entering the greenhouse.In the development of the moving object detection system, several approaches have been explored by previous researchers. One such approach involves the use of cameras to detect and track moving objects on UAVs using the segmentation method with edge-based dilation. Another study implemented a surveillance system using a webcam to detect motion and trigger an alarm to enhance security measures.This research leverages existing technologies in the areas of workflow and object recognition algorithms. These technologies are implemented in a relatively simple system capable of executing established algorithms. The primary objective is to focus on implementation that can enhance the Technology Readiness Level (TRL). The study successfully produced a security monitoring system that improves greenhouse security and assists in monitoring activities within the greenhouse. The system uses PIR (motion) sensors configured to trigger image capture by the camera and notify the ESP32 to send alerts via Telegram.